Micro, Small, and Medium Enterprises (MSME) Research on Journalistic Aspects Through Social Media Instagram - Ananda Shavana Aulia; Rosdiana .; Wahyunengsih . (Eco-Entrepreneur, 2022)
This research is entitled Micro, Small, and Medium Enterprises (MSME) Research on Journalistic Aspects Through Social Media Instagram. The purpose of the researcher in choosing this topic is because many MSMEs are experiencing obstacles in developing their business, both from internal factors and external factors. Therefore, researchers conducted research on MSMEs that use Instagram social media as a means to improve their ability to manage business on Instagram, increase promotion and market sales. This research was conducted using qualitative methods with a case research approach using data collection techniques through filling out questionnaires. The results obtained from this study can be concluded that in the digital era like today, Instagram is widely used by people of all ages as a means for selling media. In addition to its wide reach, this application also has several features that can help MSME owners promote their products, such as Instagram shopping features and advertising features.